A rare complication of testicular infarction after femorofemoral bypass highlighting the importance of surgical technique. Issue 11 (11th November 2019) - Manvar-Singh, Pallavi; Segal, Michael; Etkin, Yana; Dodla, Ranjith; Landis, Gregg; Krishnasastry, Kambhampaty V; Frankini, Larry
Abstract: We present an interesting case of a 66-year-old male who had acute testicular infarction following a right common femoral artery to left profunda femoris artery bypass with advanced symptoms of claudication. Angiography in the preoperative period demonstrated the extent of peripheral arterial disease present, revealing a calcified aorta, partially occluded left hypogastric artery, occluded left external iliac, common femoral and superficial femoral arteries and an occluded right hypogastric artery. A bypass was performed without any initial complications and subsequent relief of symptoms of claudication and rest pain. Postoperative scrotal pain and follow-up duplex demonstrated lack of perfusion of the testicle necessitating orchiectomy. This case serves to illustrate the importance of preserving collateral vessels as a technical consideration, as well as presenting a rare potential complication.